Evaluation of strategy and tactics in cycling: a systematic review of evaluation methods and possible performance implications - Cesanelli, L.; Indaburu, A. (The Journal of Sports Medicine and Physical Fitness, 2021)
INTRODUCTION: Cycling performance is affected by many factors and is the expression of a multitude of variables. Different studies aiming to describe variables determining cycling performance are focused mainly on metabolic efficiency optimization and mechanical efficiency optimization. Strategy and tactics analysis in cycling represent a key additional performance variable, however, the knowledge of methods to assess these parameters and the possible performance implications is low. The main purposes of the study were to systematically review the state of the art related to strategy and tactics analysis in cycling and describe and analyze the possible implications and possible evaluation methods of tactics and strategy in cycling. EVIDENCE ACQUISITION: MEDLINE®/PubMed and Scopus databases were searched with additional integration from external sources, between March and April 2020. To meet the inclusion criteria, studies published from 2000 to 2020 that evaluated the impact of strategies and/or tactics on cycling performance or aimed to study and develop strategy and/or tactic models to improve cycling performance were selected. EVIDENCE SYNTHESIS: Starting from the 12972 identified records, totally 22 studies met the inclusion criteria and were included in the current systematic review. Studies emerged from the selection focused mainly on time trials strategies analysis (54.55%), track cycling strategy analysis (22.73%) and other cycling disciplines strategy evaluation (road cycling, mountain bike, cyclocross; 22.73%). According to the studies` objectives, four main topics of investigation emerged from the research: evaluation of the impact of different starting strategies on time-trial performance; evaluation of different pacing strategies on performance; evaluation of aerodynamics and drag coefficients according to racing strategy in team pursuit; application of video analysis or strategy/tactics effect on performance. CONCLUSIONS: Strategy and tactics analysis in cycling represent a key additional performance variable to add to the traditionally more studied and analyzed parameters. However, few studies deeply analyzed these variables. Future works may focus on these aspects to investigate strategy and tactics insights and application of evaluation methods in cycling.